2020
DOI: 10.1093/eurheartj/ehaa227
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable plaques and patients: state-of-the-art

Abstract: Despite advanced understanding of the biology of atherosclerosis, coronary heart disease remains the leading cause of death worldwide. Progress has been challenging as half of the individuals who suffer sudden cardiac death do not experience premonitory symptoms. Furthermore, it is well-recognized that also a plaque that does not cause a haemodynamically significant stenosis can trigger a sudden cardiac event, yet the majority of ruptured or eroded plaques remain clinically silent. In the past 30 years since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 54 publications
2
78
1
Order By: Relevance
“…Therefore, the molecular mechanism of plaque rupture and erosion differ in phenotypical and functional aspects, which can explain why plaque erosion is not accompanied by detectable systemic inflammation. In general, superficial plaque erosion is mainly initiated by endothelial cell damage caused by various factors, including hemodynamic disturbance, oxidative stress, and TLR activation mediated by hyaluronic acid [ 2 , 42 ]. Injured endothelial cells covering the plaque progressively detach from the basement membrane.…”
Section: Immune and Inflammation In The Pathogenesis Of Acsmentioning
confidence: 99%
“…Therefore, the molecular mechanism of plaque rupture and erosion differ in phenotypical and functional aspects, which can explain why plaque erosion is not accompanied by detectable systemic inflammation. In general, superficial plaque erosion is mainly initiated by endothelial cell damage caused by various factors, including hemodynamic disturbance, oxidative stress, and TLR activation mediated by hyaluronic acid [ 2 , 42 ]. Injured endothelial cells covering the plaque progressively detach from the basement membrane.…”
Section: Immune and Inflammation In The Pathogenesis Of Acsmentioning
confidence: 99%
“…Morphological assessment of ruptured plaques revealed that fibrous cap thickness and a combination of large plaque burden and small lumen area result in ACS [30]. Although PCI for vulnerable coronary atherosclerotic plaques seems to be a safe procedure, a systemic pharmacotherapy rather than individual 'plaque sealing' remains the key intervention in the treatment of TCFA in non-flow limiting coronary lesions [31][32][33].…”
mentioning
confidence: 99%
“…The systemic vulnerability of patients that have suffered an acute coronary event is still a hot topic in cardiovascular research, as several predictive markers are still arising. The concept of a cardiovascular vulnerable patient refers to systemic vulnerability including systemic inflammation and increased thrombogenicity, and also local vulnerability, that encompasses unstable coronary plaques and vulnerable myocardium [ 67 ]. Both systemic and local coronary vulnerability should be included in models that can predict patient outcomes, both in the short and long term, following AMI.…”
Section: Discussionmentioning
confidence: 99%